APLIKASI FORECASTING METHODS SEBAGAI ALAT BANTU UNTUK MENDUKUNG KEBIJAKAN INVENTORY CONTROL BAHAN BAKU PADA INDUSTRI PENGECORAN LOGAM - Ag Eko Susetyo; Dian Tiara Rezalti (Teknik Industri Universitas Sarjanawiyata Tamansiswa, 2020)
PT mitra rekatama independent is a company that manufactures runs in the metal casting producing the spare parts for agricultural equipment based on orders from the customers.Some of the main problems that were visited associated with supplies of raw materials in the company is the raw material limited when the demand for products that are high and the price of raw materials. fluctuatesAssociated with the problems faced by the company then diperlukanlah a control system metal. supplies of raw materials. Economic order quantity ( EOQ ) is a methods used in control supplies raw materials by means of a request in foreseeing the future would turn up with several a method of divination .To determine a method of divination the best a check the accuracy forecasting use MAD ,MSE and MAPE minitab software with the tools .A method of divination multi decomposition is a method of what is best for the company .EOQ used to determine the quantity of reservations based on the results of forecasting , safety stock and reservations repeated raw materials. From the results of data processing these chareges in the future forming and discussion shows that of the a method of eoq produce the quantity the ticket selling is low as many as 58.585 kg / a message with the interval of a fifth 1 the ticket selling is low the ticket selling is low fed them indiana duckling mousseline order within one month ahead , safety stock 3.127 , and they would have to re the ticket selling is low at the time of reached an unprecedented level of 7.495 per kilogram which is to then made into raw materials .The total cost of a buildup in inventories can then made into raw materials metal as much as IDR 27.486.305,44Â Keywords: Supplies, EOQ, Forecasting, Multi Decomposition